SWOT analysis of Muhammad Anees & Company / Muhamad Noor Hisyamuddin Othman - Othman, Muhamad Noor Hisyamuddin (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
For the past six months, I have been blessed with the opportunity to train and gain working experience here at Muhammad Anees & Company (Penang). My name is Muhamad Noor Hisyamuddin bin Othman, a final year student of UiTM Arau majoring in Business Administration (Hons) Finance. Muhammad Anees & Company is a young and growing company that is founded by Mr. Muhammad Anees bin Sheik Othman. This company is established on 6 November of 2011 and now it has two branches which are in Penang and in Kuala Lumpur. There are 35 employees here, including permanent workers as well as internship students like I am that ranges from various ethnicity and age groups. As for my training experience, I can sum up that it has been a great and educational time for me during my internship period. I was placed in the finance department and I had learned many new things regarding financing activities such as preparing various documents such as invoices, transfer vouchers and payment vouchers. Overall, it is quite educational and useful. This study implements the SWOT analysis that covers the internal and external aspects of the company. This analysis is used as an assist to identify the company’s financial performance. This study also is made in order to center the positive and negative aspects observed while I was completing my internship at the company.